"Fighting Words": Ralph Ellison and Len Zinberg - Boddy, Kasia (American Studies, 2015)
A study of the intertextual relationship between Ralph Ellison’s _Invisble Man_ and Len Zinberg’s lesser known novel _Walk Hard–Talk Loud_ in the context of ethnic working class boxing and Popular Front approaches to sports.